2020
DOI: 10.1002/cpt.2113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pilot Vancomycin Precision Dosing Advisory Service on Target Exposure Attainment Using an Interrupted Time Series Analysis

Abstract: Therapeutic drug monitoring (TDM) of vancomycin is recommended to improve efficacy, minimize toxicity, and prevent the development of resistant microbial strains. International guidelines now recommend the use of an area under the concentration-time curve (AUC)-guided approach to optimize vancomycin dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 45 publications
2
35
0
1
Order By: Relevance
“…A number of studies have assessed the outcome of individualized dosing guided by PK tools, both in trough-based and AUC-based monitoring. 18 , 20 , 22 , 24 , 25 , 28 , 31–33 , 35 , 37–39 , 43 , 48 , 52–54 , 62–65 Through literature review of 22 studies, we found 11 studies evaluating AUC-based dosing, 18 , 22 , 24 , 28 , 48 , 52–54 , 62–64 and the other 11 studies evaluating trough-based PK-guided dosing. 20 , 25 , 31–33 , 35 , 37–39 , 43 , 65 Characteristics of the studies evaluating trough-based PK-guided dosing are summarized in Supplementary Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have assessed the outcome of individualized dosing guided by PK tools, both in trough-based and AUC-based monitoring. 18 , 20 , 22 , 24 , 25 , 28 , 31–33 , 35 , 37–39 , 43 , 48 , 52–54 , 62–65 Through literature review of 22 studies, we found 11 studies evaluating AUC-based dosing, 18 , 22 , 24 , 28 , 48 , 52–54 , 62–64 and the other 11 studies evaluating trough-based PK-guided dosing. 20 , 25 , 31–33 , 35 , 37–39 , 43 , 65 Characteristics of the studies evaluating trough-based PK-guided dosing are summarized in Supplementary Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“… 56 Compared to AUC, monitoring trough concentration is easily applicable in medical centers with a readily available serum vancomycin concentration assay. 58 Moreover, although the evidence for the recommendations has been strengthened compared to the previous guideline and a number of studies have shown better efficacy and safety outcomes through AUC monitoring since the publication of the revised guideline 18 , 22 , 24 , 28 , 48 , 52–54 , 62–64 , there are no randomized controlled trials. Given the challenging prerequisites for implementing AUC monitoring and the absence of high-quality evidence, it is still difficult to endorse conversion from trough to AUC monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that a Bayesian software DoseMe ® significantly increased the proportion of patients with severe diabetic foot infections achieving target exposure without increasing the risk of nephrotoxicity compared with empirical dosing based on Cmin ( Vali et al, 2021 ). With the induction of DoseMe ® -based pilot TDM counseling services, the proportion of patients meeting vancomycin target exposure increased significantly ( Stocker et al, 2021 ). These findings showed that Bayesian-guided dosing outperformed clinician judgment in predicting PD targets.…”
Section: Optimization Of Vancomycin Delivery For Severe Infective Pat...mentioning
confidence: 99%
“…Automated tools to select the most suitable pharmacokinetic model improve the clinical benefit from exposure guided vancomycin dosing 14 . Setting up an advisory service to guide prescribers 15 or the use of modelling tools integrated seamlessly into the electronic medical record and electronic prescribing system 16 removes much of the burden from the treating clinician to make implementation much easier. Further advances in, and the broader use of, such clinical decision support tools will help enable wider uptake for those drugs that can benefit from precision dosing.…”
Section: Goldilocks Principle: One Dose Does Not Fit Allmentioning
confidence: 99%